Bahasa Indonesia sebagai Alat Pemersatu Bangsa - I Nyoman Temon Astawa (Dharma Sastra: Jurnal Penelitian Bahasa dan Sastra Daerah, 2022)
Language is a national identity. The Indonesian nation has a unified language that is used by all its people to communicate. A great nation needs language as a unifying agent so that communication becomes easier and fosters a sense of nationalism in every area it covers. Indonesian is the language of unity that is upheld by all Indonesians. This is reflected in the third pledge of the 1928 Youth Pledge which reads, "We sons and daughters of Indonesia uphold the language of unity (national language), Indonesian", Indonesian is also the only official language nationally in Indonesia. This is in accordance with Article 36 of the 1945 Constitution. Language is the most important component in human life. Humans will not be able to continue their survival properly and regularly without language. They can not interact easily and better if they do not master the language between each other and with the absence of the continuity they can not capture the expression of psychiatric or intentions expressed by opponents of communication. It also causes the septum and less emotional affiliated with one another. It could be said that language as one of the primary needs that have a role as a regulator of the circulation of survival that is as a means of communication which might be expected with good communication Indonesian national unity can be realized. In fact, the language can also be categorized as the most powerful weapon to fortify themselves and the country from the threats of disintegration.